1999
DOI: 10.1097/00005176-199905000-00050
|View full text |Cite
|
Sign up to set email alerts
|

Immune Reaction Against Cytoskeleton in Coeliac Disease

Abstract: Background-The cytoskeleton actin network of intestinal microvilli has been found to be rapidly impaired after gluten challenge in coeliac disease (CD). The aim of this study was to investigate the presence of an immune reaction towards cytoskeleton structures such as actin filaments in CD. Methods-Eighty three antiendomysial antibody positive CD patients (52 children and 31 adults) were studied at our outpatient clinics from 1996 to 1998 using indirect immunofluorescence, ELISA, and western blotting for antia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 24 publications
4
36
0
2
Order By: Relevance
“…However, these serological tests do not correlate with histopathological features [8,18] and only recently another test -the AAA assay -has been proposed as a marker of the severity of intestinal mucosa damage in CD [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these serological tests do not correlate with histopathological features [8,18] and only recently another test -the AAA assay -has been proposed as a marker of the severity of intestinal mucosa damage in CD [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…However, these assays do not reflect the severity of the intestinal mucosa damage [7,8]. In this respect, the immunofluorescence (IF) assay of IgA anti-actin antibodies (AAA) has been suggested as a useful method [9,10] and we recently described an ELISA which demonstrated to be an accurate assay for their determination [11].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of EMA or tTGA in our study was significantly associated with more severe villous atrophy. Sensitivity of serological testing is questionable among patients presenting with PVA, thus reducing its effectiveness in clinical practice [12,18,19,22]. Rostami et al [23] show that EMA has a lower sensitivity in CD patients with milder intestinal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer data correlating serologic levels with degree of villous atrophy are available. Clemente et al [12] found IgA antibodies against actin filaments (AAA) in 60% of children and 90% of adults with severe or moderate villous atrophy caused by CD. In their study, IgA AAA were strongly correlated with more severe degrees of intestinal villous atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, this injury results in diarrhea and in malabsorption. The gliadin-induced molecular mechanisms are not yet clarified (7)(8)(9).…”
mentioning
confidence: 99%